Risk Riskreduction Reductionprinciples - Rastislav Kuliha (Communications - Scientific letters of the University of Zilina, 2001)
Various ways are applied for the attestation of a risk degree for a continuous system, with time samples for observation of the state. The neural network has been designed. The parameters of reliability have been calculated for flat power function.